التواصل غير اللفظي في القرآن الكريم سورة الكهف أنموذجا - شعيب, محمد (كلية الأدب العربي والفنون, 2025)
تعد سورة الكهف نموذجًا قرآنيًا غنيًا بتجليات التواصل غير اللفظي، حيث تتنوع فيه المواقف التي توظف الإشارة الصمت الهيئة الحركات الجسدية، والمواقف الرمزية كأدوات تواصل تحمل دلالات عميقة. ففي قصة أصحاب الكهف، نجد أن هيئتهم أثناء نومهم، وتقليب أجساد هم وبسط الكلب لذراعيه كلها إشارات غير لفظية تحمل رسائل رعب وهيبة لكل من يراهم رغم غياب أي كلام. أما في قصة موسى والخضر، فإن أفعال الخضر -كخرق السفينة وقتل الغلام -كانت رسائل غير لفظية عجز موسى عن تفسيرها في البداية، مما يعكس أهمية الأفعال كوسائل تواصل تحتاج إلى تدبر وفهم للسياق. وفي قصة صاحب الجنتين، يُظهر القرآن كيف يمكن لسلوك التفاخر أو التواضعأن يكون وسيلة تواصل غير لفظية تعكس مكنونات النفس. كذلك، تجسدت قيادة ذو القرنين من خلال الفعل العملي في بناء السد لا من خلال الخطابة، مما يعكس عمق التواصل العملي الفعال. إن هذه النماذج توضح كيف يوظف القرآن الكريم في سورة الكهف وسائل غير لفظية بشكل بلاغي وتربوي راقٍ، ما يدل على شموليته في فهم النفس البشرية وأساليب تعبيرها المتعددة، وهو ما يجعل سورة الكهف مرجعًا دقيقًا لدراسة هذا النوع من التواصل ضمن الإطار القرآني. Surat Al-Kahf is a Qur'anic model rich in manifestations of nonverbal communication, featuring a variety of situations that employ gestures, silence, posture, physical movements, and symbolic situations as communication tools carrying profound meanings. In the story of the Companions of the Cave, we find that their posture while sleeping, the turning of their bodies, and the dog's outstretched arms are all nonverbal signals that convey messages of fear and awe to all who see them, despite the absence of any words. In the story of Moses and Al-Khidr, Al-Khidr's actions—such as sabotaging the ship and killing the boy—were nonverbal messages that Moses was initially unable to interpret, reflecting the importance of actions as means of communication that require contemplation and understanding of context. In the story of the Owner of the Two Gardens, the Qur'an demonstrates how boastful or humble behavior can be a means of nonverbal communication that reflects the innermost thoughts of the soul. Likewise, Dhul-Qarnayn's leadership was embodied through practical action in building the dam, not through rhetoric, reflecting the depth of effective practical communication. These examples illustrate how the Holy Quran employs nonverbal means in Surat Al-Kahf in a sophisticated rhetorical and educational manner. This demonstrates its comprehensive understanding of the human psyche and its various modes of expression, making Surat Al-Kahf a precise reference for studying this type of communication within the Quranic framework.
Keywords: التواصل – اللفظ – القرآن الكريم – سورة الكهف.